2002
DOI: 10.1111/j.1471-0528.2002.01028.x
|View full text |Cite
|
Sign up to set email alerts
|

Histologic chorioamnionitis and umbilical serum levels of pro‐inflammatory cytokines and cytokine inhibitors

Abstract: Objective To study 1. whether leucocyte infiltration in placenta tissues is associated with elevated umbilical serum levels of inflammatory mediators, and 2. whether leucocyte infiltration in the presence of neonatal disease is associated with additional increase in mediator levels.Setting University hospital.Population Two groups of women with either normal delivery (n= 82) or delivery complicated by prolonged rupture of the membranes, clinical signs of intrauterine infection or preterm labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(38 citation statements)
references
References 21 publications
(20 reference statements)
5
32
0
1
Order By: Relevance
“…The correlation between increased levels of cytokines, IL-1b, IL-6, IL-8, sTNFR-I and sTNFR-II, and CAM has been reported in many studies. [1][2][3][4][5][6][7] In the present study, sTNFR-I was significantly increased in severe CAM. Recent investigations have demonstrated that CAM or intrauterine inflammation (or both) may be associated with a pulmonary inflammatory response that plays an important role in the development of CLD.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The correlation between increased levels of cytokines, IL-1b, IL-6, IL-8, sTNFR-I and sTNFR-II, and CAM has been reported in many studies. [1][2][3][4][5][6][7] In the present study, sTNFR-I was significantly increased in severe CAM. Recent investigations have demonstrated that CAM or intrauterine inflammation (or both) may be associated with a pulmonary inflammatory response that plays an important role in the development of CLD.…”
Section: Discussionsupporting
confidence: 62%
“…Various inflammatory cytokines (interleukin [IL]-1b, IL-6, IL-8) in umbilical cord blood have been reported in infants born to mothers with chorioamnionitis (CAM). [1][2][3][4][5] Gomez et al proposed that a fetal systemic inflammatory response syndrome (FIRS) determined by inflammatory cytokine elevation (IL-6 >11 pg/mL) in fetal blood is a risk factor for severe neonatal morbidity (i.e. sepsis, bronchopulmonary dysplasia, periventricular leukomalacia).…”
Section: Introductionmentioning
confidence: 99%
“…However, comparisons to data obtained from investigation of non-periodontal factors and cord cytokine levels revealed a slightly higher median IL-6 level in POPET study participants when compared with those of a Norwegian-based study of females with histologic chorioamnionitis. 42 This was also the finding for median levels of IL-8 and IL-1b when compared with the findings of a Spanish-based investigation of cord serum cytokines as potential predictors of neonatal sepsis. 43 Bearing in mind the findings of the current POPET study, it is possible that intrapregnancy periodontal treatment may be an ineffective intervention when attempting to target an already pregnancy-activated inflammatory cascade.…”
Section: Discussionsupporting
confidence: 56%
“…5,6 In both spontaneous preterm and term labor, this placental lesion is associated with elevated concentrations of pro-inflammatory cytokines such as IL-1α, IL-1β, TNFα, IL-8, and IL-6 in the amniotic fluid [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and umbilical cord blood. [27][28][29][30][31][32][33] Elevated concentrations of these cytokines are linked to adverse neonatal outcomes. 20,21,27,[34][35][36][37][38][39][40][41][42][43][44][45] Therefore, the study herein focused on the mechanisms implicated in acute chorioamnionitis.…”
Section: Introductionmentioning
confidence: 99%